2019
DOI: 10.3892/ol.2019.10827
|View full text |Cite
|
Sign up to set email alerts
|

BNP as a marker for early prediction of anthracycline‑induced cardiotoxicity in patients with breast cancer

Abstract: Anthracycline chemotherapy serves an important role in treating patients with breast cancer but is associated with cardiotoxicity. Although brain natriuretic peptide (BNP) is not the ideal marker for detecting the presence of diseases of the heart, several studies have demonstrated the predictive utility of BNP in the diagnosis of anthracycline-induced cardiotoxicity (AIC). The aim of the present study was to evaluate the role of BNP as a marker for the early prediction of AIC in patients with breast cancer. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Conflicting data were reported about the effects of alpha-lipoic acid on brain natriuretic peptide (BNP), tumor necrosis factor-alpha (TNF-α), malondialdehyde (MDA), and neurotensin. It has been demonstrated that there was an elevation in BNPlevel during treatment with doxorubicin [ 38 ] and ALA can ameliorate doxorubicin-associated cardiotoxicity [ 22 ] and can reduce cardiovascular events in patients on hemodialysis [ 39 ]. In contrast, a previous study revealed that there was no significant difference in BNP level between ALA group and the control group 12 months after treatment in patients with a previous experience of transient takotsubo cardiomyopathy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data were reported about the effects of alpha-lipoic acid on brain natriuretic peptide (BNP), tumor necrosis factor-alpha (TNF-α), malondialdehyde (MDA), and neurotensin. It has been demonstrated that there was an elevation in BNPlevel during treatment with doxorubicin [ 38 ] and ALA can ameliorate doxorubicin-associated cardiotoxicity [ 22 ] and can reduce cardiovascular events in patients on hemodialysis [ 39 ]. In contrast, a previous study revealed that there was no significant difference in BNP level between ALA group and the control group 12 months after treatment in patients with a previous experience of transient takotsubo cardiomyopathy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…При этом связь динамики уровня NT-proBNP с проведением противоопухолевой терапии изучена недостаточно. Установлено повышение концентрации NT-proBNP у пациентов, в лечении которых использовались антрациклины [11,12]. Однако до настоящего времени не выработано единое мнение о возможности использования этого маркера с целью оценки и прогноза кардиотоксичности химиотерапии у онкогематологических больных, поскольку эти исследования малочисленны.…”
Section: Discussionunclassified
“…However, echocardiograms cannot detect early cardiomyocyte damage and have limited reproducibility and accuracy. That said, strain imaging with echocardiography may show subclinical dysfunction during chemotherapy or sepsis before decline in EF by objectively quantifying myocardial mechanical function 10 . B‐type natriuretic peptide (BNP) has also been suggested for detection of early cardiac dysfunction from anthracyclines.…”
Section: Discussionmentioning
confidence: 99%
“…Based on research from Lu et al. (2019), 10 BNP elevation may be more sensitive than echocardiogram for predicting cardiotoxicity. COG's new trial (AAML1831) will utilize strain echocardiogram and cardiac markers such as BNP to determine the utility of sensitive measures of cardiac function in predicting cardiotoxicity in children with AML.…”
Section: Discussionmentioning
confidence: 99%